Patients with hypertension and chronic kidney disease as a priority group for primary prevention programs - E. A. Medvedeva; E. I. Usova; A. E. Solovyova; M. V. Dubinina; S. V. Villevalde; N. E. Zvartau; E. V. Shlyakhto (Российский кардиологический журнал)
The combination of hypertension and chronic kidney disease is a stage of the cardiovascular-renal-metabolic continuum and associated with adverse cardiovascular and renal outcomes. Epidemiological aspects, accessible screening algorithm within outpatient monitoring, availability of modern cardiac and renal protective strategies make it possible to select this high-risk group as a priority for the implementation of effective targeted primary prevention and maintaining the trend of reducing cardiovascular morbidity and mortality in the medium- and long-term.